Efficacy and effectiveness of alcohol in the disinfection of semi-critical materials: a systematic review - Maíra Marques Ribeiro; Verena Ashley Neumann; Maria Clara Padoveze; Kazuko Uchikawa Graziano (Universidade de São Paulo, 2015)
AbstractObjective: to assess the efficacy and the effectiveness of 60-80% alcohol (v/v) in the disinfection of semi-critical materials which were either previously cleaned or not.Method: studies obtained from BIREME, IBECS, MEDLINE, ScIELO, PubMed, Ask Medline web portals, and references from other studies. Criteria were created to assess the methodological quality of articles. Out of the 906 studies found, 14 have been included.Results: after materials were disinfected with alcohol, microorganisms were detected in 104/282 (36.9%) effectiveness tests and in 23/92 (25.0%) efficacy tests that were conducted. In the field studies, disinfection was not achieved for 74/218 (33.9%) of the products that were submitted to previous cleaning and for 30/64 (46.9%) of the ones which were not submitted to previous cleaning. In the experimental studies, alcohol disinfection was not efficacy in 11/30 (36.7%) and 12/62 (19.4%) of products, respectively. The studies were not found to have followed standardized methods.Conclusion: disinfection of semi-critical products with alcohol 70% - or in an approximate concentration - cannot be recommended to all health care products in an unrestricted way. However, according to the type of semi-critical product, disinfection can be attained with or without previous cleaning.